Investigation of Phase Delay Dispersion of the Meander Lines using Hybrid Technique - Gurskas, Antanas; Krukonis, Audrius; Urbanavicius, Vytautas (Elektronika ir Elektrotechnika, 2015)
Periodical slow-wave systems, for example helical or meander delay lines are dispersive. I. e. velocity of propagation of electromagnetic wave in such systems, or delay time of a signal in the correspondent line, depends on wave frequency. This fact reduces the bandwidth of such systems or lines, even if losses are totally absent in it. Delay dispersion of such systems at high frequencies can be explained by coupling of adjacent conductive strips and the frequency properties of the dielectric materials. However, the dispersion at low frequencies, hardly investigated until now. The sources of phase delay dispersion of the meander microstrip delay lines and some other slow-wave systems at low frequency range are investigated in this paper. To study the dispersion of delay systems mathematical and computer modelling, and experimental measurements were used. DOI: http://dx.doi.org/10.5755/j01.eee.21.2.115010